Analysis of Mathematical Concept Under the Review of Students Learning Interest in Solving Algebraic Problems - Kariimah, Hasnna; Fatikhah, Findi Auliya (Faculty of Tarbiya and Teacher Trainning, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
This research aims to analyze the influence of the level of interest in learning on the understanding of mathematical concepts by seventh-grade students at As-Subkiyah Junior High School in Kota Bekasi when solving algebraic problems. Understanding mathematical concepts is a crucial foundation for effective mathematics learning, but students often face difficulties in grasping these concepts. The research method employed is descriptive qualitative research. Data were obtained through learning interest questionnaires and tests assessing mathematical concept comprehension. The research subjects are seventh-grade students at As-Subkiyah Junior High School in Kota Bekasi. The results indicate that students' mathematical concept comprehension can be influenced by their level of learning interest. Students with high learning interest have excellent concept comprehension and can master all the tested indicators. Students with moderate learning interest have sufficient comprehension, although they can only master some of the tested indicators. Meanwhile, students with low learning interest still struggle to understand mathematical concepts well and can only master a small portion of the tested indicators. The research identified several understanding errors among students, such as misconceptions about variables, terms, coefficients, and constants in algebraic expressions.